The Influence of Teacher's Authority on The Formation of Students' Materials - Muhamad Hidayatullah; Sufinatin Aisida (Journal Analytica Islamica, 2023)
Having and maintaining credibility is essential and absolutely necessary when fulfilling the role of an educator. With credibility, a teacher can provide guidance and advice to students without the need for coercion. If credibility is lost, students may become emboldened to oppose authority, which they initially respected. This indicates that the school's values, rules, and even the teacher's instructions may not be respected. Therefore, education cannot effectively proceed without credibility. In this context, the teacher's role in shaping morals becomes even more prominent, with credibility as the key factor driving this process. It is crucial to instill moral values in the younger generation, especially students, so they are not easily influenced by their surroundings and can adapt themselves according to the Islamic educational goal of fostering individuals who are faithful, pious, and morally upright. This research employed quantitative research methods, specifically correlation analysis. The findings revealed that teacher credibility was rated at 75.42%, considered good as it falls within the 61%-80% interval. The assessment of students' moral development scored 72.73%, also falling within the 61%-80% interval, indicating a good level of moral development. The correlation coefficient, rxy, was calculated as 0.793, indicating a strong influence. In conclusion, this study demonstrates a strong correlation between teacher credibility and students' moral development, which is crucial for achieving the goal of creating morally upright individuals in Islamic education. Memiliki dan menjaga kewibawaan merupakan hal yang esensial dan mutlak diperlukan dalam menjalankan peran sebagai pengajar dan pendidik. Dengan memiliki kewibawaan, seorang guru dapat memberikan petunjuk dan nasihat kepada peserta didik tanpa adanya rasa paksaan. Jika kewibawaan hilang, maka peserta didik mungkin akan merasa berani untuk menentang, yang pada awalnya mereka patuh terhadap kewibawaan guru. Ini mengindikasikan bahwa tata nilai sekolah, aturan, dan bahkan petunjuk guru tidak akan dihormati. Dengan demikian, pendidikan tidak akan berjalan efektif tanpa adanya kewibawaan. Dalam hal ini, peran guru dalam membentuk akhlak menjadi semakin menonjol, dengan kewibawaan sebagai faktor kunci yang menggerakkan proses ini. Maka, sangat penting untuk melakukan pembentukan akhlak pada generasi muda, terutama peserta didik, agar mereka tidak mudah terpengaruh oleh lingkungan sekitarnya dan mampu menyesuaikan diri sesuai dengan tujuan pendidikan Islam yang bertujuan membentuk pribadi muslim yang beriman, bertaqwa, dan berakhlak baik. Pembentukan akhlak memiliki peran penting dalam mewujudkan individu yang memiliki ketaqwaan kepada Allah SWT. Penelitian ini menggunakan metode penelitian kuantitatif dan jenis penelitian korelasi. Hasil penelitian ini pada analisis persentase kewibawaan guru diperoleh hasil nilai 75,42% dan tergolong baik, karena berada pada interval 61%-80%. Pada analisis pembentukan akhlak mahmudah peserta didik diperoleh hasil 72,73% dan tergolong baik, karena berada pada interval 61%-80%. pada analisis product moment dengan nilar rxy = 0,793 dan pada tabel interpretasi koefisien korelasi di atas menyatakan bahwa nilai “r” yang diperoleh berada pada taraf 0,60-0,799 sehingga tergolong memiliki pengaruh kuat.